Analysis of Palm Oil Processing at PT XYZ in North Morowali Regency - Nadila Hance; Dhian Herdhiansyah; Muh Syukri Sadimantara; Asriani Asriani (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to determine the production process of crude palm oil and determine the quality control of crude This study aims to determine the crude palm oil production process at PT. XYZ in North Morowali Regency. The determination of the research location was carried out purposefully. The research subjects are the parties involved in the research, namely PT. XYZ and the object of research is the production of crude palm oil. Data collection was carried out using historical data methods and literature studies. The results showed that the crude palm oil production process started with (a) fruit harvesting; (b) transportation of FFB; (c) receipt and sorting of FFB; (d) boiling station (sterilizer); (e) Threshing Station; (f) Pressing Station; and (g) Clarification Station.